Analyzing the impact of supply chain innovation as a mediator for healthcare firms' performance. (2022) - Pal, Surya Kant; Baral, Manish Mohan; Mukherjee, Subhodeep; Venkataiah, Chittipaka; Jana, Bhaswati
Abstract: The research is done to identify the constructs which affect the performance of a healthcare firm. Specifically, a mediating variable has been utilized to establish a relationship between the latent and dependent variables. The proposed model consists of three latent variables: vendor cooperation, SC efficiency, and quality measurement practices on afirm's performance through a mediator SC innovation. This model was developed using exploratory factor analysis and validated utilizing structural equation modeling. Information was collected from 310 respondents from various healthcare centers. The output suggested the proposed constructs significantly affected the firm's performance and contributed towards the goodness of fit. The output also indicates that a firm performance can be improvised through continuous SC innovation and cooperation with vendors, resulting in the firm's performance. Data utilized in this research were collected from various healthcare centers of India. The generalization of the results may be limited to hospitals in developingcountries. This research provides valuable information on planning in the healthcare segment. The outputs suggested firm's performance improvement is attained through continuous SC innovation.